Head first mobile web - Gardner, Lyza Danger (Head first series, 2012)
Despite the huge number of mobile devices and apps in use today, your business still needs a website. You just need it to be mobile. Head First Mobile Web walks you through the process of making a conventional website work on a variety smartphones and tablets. Put your JavaScript, CSS media query, and HTML5 skills to work--then optimize your site to perform its best in the demanding mobile market. Along the way, you'll discover how to adapt your business strategy to target specific devices. Navigate the increasingly complex mobile landscapeTake both technical and strategic approaches to mobile w.